2018
DOI: 10.4018/ijbir.2018070103
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Organizational Factors for Successful Business Intelligence Implementation

Abstract: Business intelligence (BI) has proliferated due to its growing application for business decision support. Research on organizational factors may offer significant use in BI implementation. However, a limited number of studies focus on organizational factors for revealing adverse impacts on effective decision support. The aim of this theoretical study is to conduct a literature analysis to identify organizational factors relevant to BI implementation. Through a systematic literature review, a qualitative conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…With regards to this, the previous study by Eisenhardt (1993) had also revealed that poor training and insufficient competencies as obstacles to implementation. Miller, Wilson, and Hickson (2004) and the other by study Ali and Hadi (2012) have also found that the lack of competencies and inadequate skills among employees can hindered the success of strategy implementation.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…With regards to this, the previous study by Eisenhardt (1993) had also revealed that poor training and insufficient competencies as obstacles to implementation. Miller, Wilson, and Hickson (2004) and the other by study Ali and Hadi (2012) have also found that the lack of competencies and inadequate skills among employees can hindered the success of strategy implementation.…”
Section: Discussionmentioning
confidence: 97%
“…Unpredictable changes in the environmental factors such as attitude of local populace, inflation rate, physical and site conditions can have impact on strategy implementation. The findings of the studies by Taslak ( 2004) and Ali and Hadi (2012) have also indicated environmental factors as an obstacle to effective strategy implementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations